Mechanisms for Autonomous Management of Networks and Services 4th International Conference on Autonomous Infrastructure, Management, and Security, AIMS 2010, Zurich, Switzerland, June 23-25, 2010, Proceedings - Stiller, Burkhard; De Turck, Filip (Computer Communication Networks and Telecommunications, 2010)
The International Conference on Autonomous Infrastructure, Management and Se- rity (AIMS 2010) was a single-track event integrating regular conference paper s- sions, tutorials, keynotes, and a PhD student workshop into a highly interactive event. The main goal of AIMS is to look beyond borders and to stimulate the exchange of ideas across different communities and among PhD students. AIMS 2010 collocated the International Summer School in Network and Service Management (ISSNSM 2010). This unique summer school offers hands-on learning experiences in network and service management topics, which requires attendees to work in practical on-site courses combined with preceding short tutorial-like teaching sessions. AIMS 2010--which took place during June 23-25, 2010, in Zürich, Switzerland and was hosted by the Communication Systems Group CSG, Department of Inform- ics IFI, of the University of Zürich UZH--followed the already established tradition of an unusually vivid and interactive conference series in terms of the fourth conf- ence, after successful instantiations in Oslo, Norway 2007, Bremen, Germany 2008, and Enschede, The Netherlands 2009. AIMS 2010 focused especially on autonomous management aspects of modern networks and their services. The set of mechanisms, peer-to-peer-based schemes, scalability aspects, and autonomous approaches are of major interest. In particular the design, monitoring, management, and protection of networked systems in an efficient, secure, and autonomic manner are key to comm- cially viable and successful networks and services.